Phytochemical and Toxicity Screenings in Different Parts of Eleiodoxa conferta - Nishalani Thivakar (2019)
The potential of much of the indigenous fruits are still undiscovered. Recently, researchers are giving attention to discover the locally available fruits that may have potential to use for therapeutic remedies. One of the underutilized fruits which has been consumed by the rural communities in Malaysia is Eleiodoxa conferta fruit which is locally known as ‘Buah Kelubi’. This project was conducted to screen phytoconstituent and toxicity activities of different parts of E. conferta by using different solvents extraction. Types of solvent used to extract the different parts of these fruit were 100% ethanol, 50% ethanol and water. The total phenolic content (TPC) and total flavonoid content (TFC) were studied by using Folin-Ciocalteu method and Aluminium chloride colorimetric method. Besides, phytochemical sreening was done to screen the bioactive compounds which can be further studied for development of medicinal remedies. The toxic activity of different parts of E. conferta was tested by using Brine Shrimp Lethality Assay (BSLA). The mortality percentage of a simple zoological organism-brine shrimp (Artemia salina) was tested to identify the toxicity of different parts of fruits. All data were analysed using Minitab software version 18.0. The results revealed that the content of TPC and TFC were significantly different in different parts of E. conferta. The ethanol (50% v/v) was found to be the best extraction solvent for extraction yield, TPC, and TFC. The peel extract showed the highest yield at 34.77% whereas the lowest yield was shown in seed extract at 4.89%. Besides, the highest content of TPC and TFC were found in the peel part of E. conferta fruit. Moreover, the presence of bioactive compounds and level of toxic activity have found to be significantly different in different parts of E. conferta. Therefore, it was concluded that E. conferta is beneficial for human health and it should be further studied to use it in the development of drugs.